Tonality as a textual category (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
In the focus of the author’s attention are differences between two linguistic categories – tonality as a textual category and modality as a grammar category. Separate tones are examined in the capacity of constituents of the category of tonality: the basic tone that reflects the idea in a piece of fiction and local tones that are subordinate to the tone-determinant. The variety of tones makes up the polyphony of the text which is the total tonality characteristic.
Keywords: tone; tonality; modality; polyphony